2009
DOI: 10.1158/1535-7163.mct-09-0027
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms of irinotecan sensitivity in colorectal cancer cell lines

Abstract: Irinotecan is a topoisomerase-I (Top-I) inhibitor used for the treatment of colorectal cancer. DNA demethylating agents, including 5-azacytidine (5-aza), display synergistic antitumor activity with several chemotherapy drugs. 5-Aza may enhance irinotecan cytotoxicity by at least one of the following mechanisms: (a) Top-I promoter demethylation, (b) activation of genes involved in Top-I transcriptional regulation (p16 or Sp1), and (c) modulation of the cell cycle and apoptosis after DNA damage. The growth-inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Some showed that DAC enhanced susceptibility to CPT (22,23,25,29), which is consistent with our data. In our study, DAC achieved 3-fold increase of susceptibility to CPT in the colon cancer cell line, HCT116 cells harboring DEXI methylation.…”
Section: Discussionsupporting
confidence: 93%
“…Some showed that DAC enhanced susceptibility to CPT (22,23,25,29), which is consistent with our data. In our study, DAC achieved 3-fold increase of susceptibility to CPT in the colon cancer cell line, HCT116 cells harboring DEXI methylation.…”
Section: Discussionsupporting
confidence: 93%
“…For example, promoter hypermethylation of p16 Ink4a or cytoplasmic p16 Ink4a sequestration by AE1 has been identified as changes that allow malignant transformation. Therefore, demethylating therapies or inhibition of p16 Ink4a sequestering proteins (AE1) could restore p16 Ink4a and induce premature senescence in cancer cells (Schmitt et al, 2007;Schwabe and Lubbert, 2007;Shen et al, 2007;Crea et al, 2009). It has also been shown that DNA-damaging and differentiation-inducing anticancer therapies can provoke senescence as part of their anticancer effect (Schmitt et al, 2007).…”
Section: P16 Ink4a and Treatmentmentioning
confidence: 99%
“…47 Few studies have assessed the potential predictive value of p16 in colorectal cancer in vitro and in vivo. 52,53 However, Kamoshida and colleagues compared p16 and thymidylate synthase expression in preoperative biopsies and postsurgical Original Article…”
Section: Original Article 4480mentioning
confidence: 99%